Isoform Sequencing Provides Insight Into Freezing Response of Common Wheat (Triticum aestivum L.) - Zheng, Xingwei; Shi, Mengmeng; Wang, Jian; Yang, Na; Wang, Ke; Xi, Jilong; Wu, Caixia; Xi, Tianyuan; Zheng, Jun; Zhang, Jiancheng (Frontiers in Genetics, 2020)
The objective of the study is to reveal the freezing tolerance mechanisms of wheat by combining the emerging single-molecule real-time (SMRT) sequencing technology PacBio Sequel and Illumina sequencing. Commercial semi-winter wheat Zhoumai 18 were exposed to -6℃ for 4h at the four-leaves stage. Leaves of the control group and freezing treated group were used to perform cDNA library construction. PacBio SMRT sequencing yielded 51, 570 high quality isoforms from leaves of control sample of Zhoumai 18, encoded by 20, 366 gene loci. In total, 73, 695 transcript isoforms, corresponding to 23, 039 genes were identified from the freezing treated leaves. Compared with transcripts from the IWGSC RefSeq v1.1, 57, 667 novel isoforms were discovered, which were annotated 21, 672 known gene loci, as well as 3, 399 novel gene loci. Transcriptome characterization including alternative spliced events, APA sites, transcription factors (TF) and fusion transcripts were also analyzed. Freezing-responsive genes and signals were uncovered and proved that the ICE-ERF-COR pathway and ABA signal transduction play a vital role in the freezing response of wheat. In this study, PacBio sequencing and Illumina sequencing were applied to investigate the freezing tolerance in common wheat, and the transcriptome results provide insights into the molecular regulation mechanisms under freezing treatment.